CONFLICTS IN THE PEDAGOGICAL STAFF OF THE INSTITUTION OF HIGHER EDUCATION: CAUSES OF OCCURRENCE AND WAYS OF PREVENTION - Natallia Р. Volkova (Alfred Nobel University Publisher, 2019)
The article is devoted to the disclosure of the essence, analysis of the causes of conflicts in the pedagogical team of the institution of higher education. It is noted that differences and contradictions, which are the causes of conflicts, are especially aggravated when introducing innovations, in particular those that are currently accompanying the system of higher education. The emphasis is on the need to organize the activities of the members of teaching staff, which excludes or minimizes the probability of conflicts between them; on the prevention of conflicts, which includes their prediction (involves systematic and continuous study of educational processes, moral and psychological climate of the team with a view to establishing the forecast (probabilistic judgment) about their emergence, prospects for development, future state), and on a set of preventive measures aimed at preserving and strengthening normal pedagogical relationships. Some strategies (preventive strategy of behavior by J. Scott), methods of conflict prevention (cognitive, motivational, activity, organizational), types of typical conflict generating agents, expediency of awareness of their own actions by teachers who enter into professional interaction are revealed. The necessity of systematic study and analysis of factors that increase the probability of conflict occurrence in the pedagogical team is shown by means of psychological diagnostics of personal individual and psychological peculiarities of members of the work team; the peculiarities of their cognitive sphere; motives, goals, values both as separate members of the team and the team as a whole; formal and informal structure of the team; style of leadership; the presence of micro-groups and the nature of the relationship between them and their leaders, etc. The emphasis is made on the feasibility of A. Lebedev's method, in which the depth of forecast is determined by a number of indicators, each of which reveals a certain aspect in the prediction of an interpersonal work conflict.